Effects of low-level laser therapy and therapeutic ultrasound on Freund’s complete adjuvant-induced knee arthritis model in rats - Sıtkıcan Okur; Zafer Okumuş (Archives of Rheumatology, 2023)
Objectives: The aim of this study was to evaluate and monitor the effect of low-level laser therapy (LLLT) and therapeutic ultrasound (TU) alone, or combined with intra-articular prednisolone (P) in Freund’s complete adjuvant (FCA)-induced knee arthritis model in rats. Materials and methods: A total of 56 adult male Wistar rats were divided into seven groups: control (C), disease control (RA), P, TU, LLLT (L), P + TU (P+TU), P + LLLT (P+L) groups. The skin temperature, radiography, joint volume, serum rheumatoid factor (RF), interleukin (IL)-1β, serum tumor necrosis factor-alpha (TNF-α), and histopathological evaluation of joint were performed. Results: Thermal imaging and radiographic examination provided results consistent with the severity of the disease. The mean joint temperature (°C) was the highest in the RA (36.2±1.6) group on Day 28. The P+TU and P+L groups significantly decreased radiological scores at the end of the study. The rat serum TNF-α, IL-1β, and RF levels in all groups were significantly higher compared to the C group (p<0.05). Compared to the RA group, serum TNF-α, IL-1β, and RF levels were significantly lower in the treatment groups (p<0.05). The P+TU and P+L group was showed minimal chondrocyte degeneration and cartilage erosion and mild cartilage fibrillation and mononuclear cell infiltration of synovial membrane compared to the P, TU, and L group. Conclusion: The LLLT and TU effectively reduced inflammation. In addition, a more effective result was obtained from the use of LLLT and TU combined with intra-articular P. This result may be due to insufficient dose of LLLT and TU, thus further studies should be focus on at higher dose ranges on FCA arthritis model in rats.